PKM Pelatihan Implementasi RPS OBE: Rencana Pembelajaran Semester Berbasis Outcome-Based Education di Insip Jawa Tengah - Ridwan; Niken Rahmawati; Mukholidin (Jurnal PKM Merah Putih, 2025)
The urgency of this training arises from the need to improve the quality of learning in institutions. The Implementation Method starts from: a) Socialisation and Preparation; Identification of Participants and Material Resource Persons. b) The implementation of the Training includes: OBE Theory, Implementation of RPS Preparation, and Diction. c). Evaluation and Feedback; Surveys and Follow-Ups. As a result, 30 lecturers from various departments at the Pemalang Islamic Religious Institute actively participated in the OBE Semester Lecture Plan (RPS) training. It starts on Wednesday, September 10, 2025, at the INSIP Hall of Central Java. As well as feedback, 85% of participants felt they had a better understanding of the concept of OBE and how to compile an effective RPS. Next Generated RPS: Each group successfully compiled an RPS for their course, which included learning outcomes, learning methods, and evaluation. In conclusion, the PKM training for the implementation of the OBE RPS at the Pemalang Islamic Religious Institute has succeeded in improving the skills and understanding for lecturers in the preparation of RPS in accordance with the Standards with the OBE principles. The novelty in this training lies in the innovative approach and use of renewable digital technology.